Strategi Komunikasi Public Relations Pt. Indomedia Dalam Promosi Media Sosial Berbasis Model Aisas - Bellanda Putri Rendyna; Lina Sinatra Wijaya (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study is motivated by the suboptimal effectiveness of PT Indonesia Media Komunikasi Masyarakat’s digital promotion in encouraging audience responses on social media. Although the company has used Instagram and TikTok as promotional platforms, audience engagement at each stage of the consumer behavior remains suboptimal. The research aims to analyze the public relations communication strategy of PT Indonesia Media Komunikasi Masyarakat in promoting its internet services through social media based on the AISAS (Attention, Interest, Search, Action, Share) model. This study employs a qualitative approach, using in-depth interviews with the company owner, marketing and social media staff, and customers of PT Indomedia as primary data sources. The collected data were analyzed descriptively to illustrate the implementation of communication strategies at each stage of the model. The findings reveal that although the company has implemented a structured public relations communication strategy, promotional activities have primarily focused on the attention and interest stages, while the search, action, and share stages have not yet been optimized.